The effect of route presentation and climbing strategy in competitive bouldering. The relation between observation and memorization of the route - Sugi, T.; Ishihara, M. (Japanese Journal of Sport Psychology, 2019)
In free-climbing competitions, an observation of the wall is made before the actual climbing by the competitor, that is indispensable for the later action performance. In the present study, we aimed to investigate the functional characteristics of the climber`s memory needed to prepare for the later climb. In Experiment 1, the effects of the visual presentation (i.e., real wall and monitor wall conditions) and the route type (i.e., easy, difficult, and impossible conditions) of the climbing route were examined. In Experiment 2, using a real wall, the effects of action (i.e., "with" actual moves usually used to climb and "without" moves during a given observation time) and the route type (i.e., possible and impossible) of the climbing route were examined. In those experiments, participants were asked to subtract numbers as a distraction task just after the observation of the route. They were then asked to recall the route by reporting the holds they memorized. The results showed an effect for the route type, that is, the participants showed a higher score in the easy route than in the difficult and impossible routes, particularly for the real wall condition (Experiment 1). The recall performance for the real climbing route appeared to be independent from the action ( "with" and "without"), but the recall was modulated by the route type, namely a higher score was shown in the possible route than in the impossible route (Experiment 2). These findings imply that participants might maintain a certain representation of a given route in their memory, such as the route difficulty or the possibility to move, particularly if they observed a real wall.